2022
DOI: 10.3390/ijms23147992
|View full text |Cite
|
Sign up to set email alerts
|

miR-143-3p Inhibits Aberrant Tau Phosphorylation and Amyloidogenic Processing of APP by Directly Targeting DAPK1 in Alzheimer’s Disease

Abstract: The neuropathology of Alzheimer’s disease (AD) is characterized by intracellular aggregation of hyperphosphorylated tau and extracellular accumulation of beta-amyloid (Aβ). Death-associated protein kinase 1 (DAPK1), as a novel therapeutic target, shows promise for the treatment of human AD, but the regulatory mechanisms of DAPK1 expression in AD remain unclear. In this study, we identified miR-143-3p as a promising candidate for targeting DAPK1. miR-143-3p directly bound to the 3′ untranslated region of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…Recently, miR-143-3p was reported to bind to the 3′ untranslated region of DAPK1 mRNA to inhibit its translation, thereby attenuating the phosphorylation of APP and reducing the production of Aβ 40 and Aβ 42 . 133 In addition, miR-143-3p reduced tau protein phosphorylation and promoted neural bump and microtubule assembly. The expression of miR-143-3p and DAPK1 were negatively correlated.…”
Section: Dapk1 In Diseasesmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, miR-143-3p was reported to bind to the 3′ untranslated region of DAPK1 mRNA to inhibit its translation, thereby attenuating the phosphorylation of APP and reducing the production of Aβ 40 and Aβ 42 . 133 In addition, miR-143-3p reduced tau protein phosphorylation and promoted neural bump and microtubule assembly. The expression of miR-143-3p and DAPK1 were negatively correlated.…”
Section: Dapk1 In Diseasesmentioning
confidence: 99%
“…The expression of miR-143-3p and DAPK1 were negatively correlated. Therefore, miR-143-3p may play a role in regulating the abnormal tau phosphorylation and amyloidosis process of APP by targeting DAPK1, and this regulatory mechanism may grant a new strategy for AD treatment 133 (Table 3). Apart from regulating APP and tau, DAPK1 is also involved in neurotoxic agents such as ceramide or neuronal cell death in animal models of AD.…”
Section: Dapk1 In Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the role of ncRNAs in nervous system diseases has been further refined, and in-depth studies on the physiological functions of a specific ncRNA have gradually shown a potential correlation with AD ( Jiang et al, 2022 ). For example, miR-143-3p has been found to inhibit abnormal Tau phosphorylation in AD and amyloid processing in amyloid precursor protein ( Wang L. et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%